Study of Factors Affecting Vibration Damping Properties of Multilayer Composite Structures - Vasina, Martin; Hruzik, Lumir; Burecek, Adam (Manufacturing Technology Journal, 2020)
At the present time, mechanical vibration is undesirable in many cases. Therefore it is necessary to minimize unwanted vibrations in any appropriate manner. This paper is focused on a study of factors influencing vibration damping properties that were investigated using multilayer composite structures. Frequency dependencies of the displacement transmissibility over a frequency range of 2?1500 Hz were determined by the method of forced oscillations. It was found in this study that the vibration damping properties of investigated multilayer structures are significantly influenced by number of material layers, excitation frequency of mechanical vibration, applied materials in multilayer structures, inertial mass, material thickness and density. It was also observed that a superior ability to damp mechanical vibration leads to a shift of the first resonance frequency peak position to lower excitation frequencies.
Keywords: Multilayer Structure; Harmonically Excited Vibration; Displacement Transmissibility; First Resonance Frequency; Stiffness.